Bone morphogenetic protein 2-induced human dental pulp cell differentiation involves p38 mitogen-activated protein kinase-activated canonical WNT pathway - Yang, Jing; Ye, Ling; Hui, Tian-Qian; Yang, Dong-Mei; Huang, Ding-Ming; Zhou, Xue-Dong; Mao, Jeremy J; Wang, Cheng-Lin (International journal of oral science, 2015)
Both bone morphogenetic protein 2（BMP2） and the wingless-type MMTV integration site（WNT）/p-catenin signalling pathway play important roles in odontoblast differentiation and dentinogenesis.Cross-talk between BMP2 and WNT/p-catenin in osteoblast differentiation and bone formation has been identified.However,the roles and mechanisms of the canonical WNT pathway in the regulation of BMP2 in dental pulp injury and repair remain largely unknown.Here,we demonstrate that BMP2 promotes the differentiation of human dental pulp cells（HDPCs） by activating WNT/p-catenin signalling,which is further mediated by p38mitogen-activated protein kinase（MAPK） in vitro.BMP2 stimulation upregulated the expression of p-catenin in HDPCs,which was abolished by SB203580 but not by Noggin or LDN193189.Furthermore,BMP2 enhanced cell differentiation,which was not fully inhibited by Noggin or LDN193189.Instead,SB203580 partially blocked BMP2-induced p-catenin expression and cell differentiation.Taken together,these data suggest a possible mechanism by which the elevation of p-catenin resulting from BMP2 stimulation is mediated by the p38 MAPK pathway,which sheds light on the molecular mechanisms of BMP2-mediated pulp reparative dentin formation.